TI_GERICHTE 52.2024.119 vom 6. März 2024 , Commesse pubbliche. Esclusione per superamento preventivo. Attendibilità del preventivo - TI Tribunale d'appello (2024)
Commesse pubbliche. Esclusione per superamento preventivo. Attendibilità del preventivo